Educational actions as reduction strategies for diabetic foot - Schulz, Renata da Silva; de Moura, Brisa Alves Pereira; Barreto, Ana Samira Madureira Lordelo; Santana, Monique Santos; Rabêlo, Júlia Pereira (Journal of Health Care, 2016)
Objective: To characterize the educational actions used in clinical practice for patients with diabetic foot based on scientific productions. Method: An integrativereview was carried out in July 2015 in the electronic databases Medline, PubMed, Cumed, and SciELO using the association of descriptors: diabetes mellitus, diabetic neuropathies, health care, foot ulcer, primary prevention. Studies published between 2010 and 2015 were included, while the criteria for exclusionwas based on articles concerning the care of ulcers that were already established, articles whose methodology was related to editorials about the issue, and repeated articles. Results: A total of 88 scientific papers were found. After selection, eight studies were included. All of them showed health education and patient adherence to interventions proposed as the key points to be worked in ambulatory practice. Conclusion: The specialized treatment to prevent complications in the lower limbs of patients as well as encouraging self-care/self-control are essential for the strategies involved. The patient should be encouraged to actively participate in treatment, being guided for awareness about the disease as well as for the promotion, prevention and recovery of health.
Keywords: diabetes mellitus; diabetic neuropathies; health care; foot ulcer; primary prevention